2017
DOI: 10.1002/anie.201707914
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Transfer and Hydride‐Transfer Pathways in the Stoltz–Grubbs Reducing System (KOtBu/Et3SiH)

Abstract: Recent studies by Stoltz, Grubbs et al. have shown that triethylsilane and potassium tert‐butoxide react to form a highly attractive and versatile system that shows (reversible) silylation of arenes and heteroarenes as well as reductive cleavage of C−O bonds in aryl ethers and C−S bonds in aryl thioethers. Their extensive mechanistic studies indicate a complex network of reactions with a number of possible intermediates and mechanisms, but their reactions likely feature silyl radicals undergoing addition react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Although a broad network of reactions involving several intermediates and mechanisms has been proposed, the mechanistic diversity of this pair of reagents is still puzzling. We recently reported the Et 3 SiH/KO t Bu reagent in reductions of arenes and in cleavage of C−N bonds . In this article, we report our experimental and computational studies on the use of this reagent pair to silylate amines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a broad network of reactions involving several intermediates and mechanisms has been proposed, the mechanistic diversity of this pair of reagents is still puzzling. We recently reported the Et 3 SiH/KO t Bu reagent in reductions of arenes and in cleavage of C−N bonds . In this article, we report our experimental and computational studies on the use of this reagent pair to silylate amines.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the Et 3 SiH/KO t Bu reagent in reductions of arenes and in cleavage of CÀ N bonds. [31] In this article, we report our experimental and computational studies on the use of this reagent pair to silylate amines. Our publication at this stage is prompted by the appearance of a very recent patent in this area.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Grubbs et al . reported that heating Et 3 SiH with KO t Bu afforded a novel reagent which has since been shown to carry out a wide range of chemical transformations . (Schemes and ).…”
Section: Introductionmentioning
confidence: 99%
“…at lower temperatures, cleavage of Ar−O bonds in aryl ethers 3 , and Ar−S bond cleavage in thioethers 5 at higher temperatures. In addition, the reagent debenzylates N‐benzylindoles, 7 , reduces fused aromatic hydrocarbons, ( e.g . 9 ) to their dihydro counterparts, and converts primary and secondary amines, e. g. 11 to their silylated derivatives, in this case, 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation